Work engagement and employee well-being : psychosocial support to build engaged human capital - Adamska-Chudzińska, Małgorzata; Pawlak, Justyna (Routledge research in human resource management., 2025)
Work Engagement and Employee Well-being highlights the vital role of psychosocial support in building and stimulating work engagement. It is a response to the growing phenomenon of weakened employee attachment and engagement instability. The authors underscore the importance of creating a friendly work environment, which accommodates a variety of employee needs and elicits positive emotions, thus fostering the well-being and complete engagement of employees. An in-depth literature review and empirical research conducted using combined qualitative and quantitative methods enabled the authors to present the issue from a wide range of theoretical perspectives. With a model acknowledging the multifaceted nature of work engagement and its association with well-being, the book introduces a selection of psychosocial means to enhance it. The analysis focuses on both systemic measures, that is, promoting a supportive organizational culture and protecting work-life balance, as well as a more individualized approach that not only facilitates the recognition and respect of employee needs but also helps cultivate their development. The book places emphasis on a transformational leadership style and a high level of emotional intelligence among managers, particularly their empathy. Further attention was paid to the various ways to support specific employee groups, such as remote workers and neurodivergent members of the workforce.